2014
DOI: 10.1007/s10571-014-0140-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RBMX in the Light-Induced Damage of Rat Retina In Vivo

Abstract: RNA-binding motif protein, X-linked (RBMX) is a 43 kDa nuclear protein in the RBM family and functions on alternative splicing of RNA. The gene encoding RBMX is located on chromosome Xq26. To investigate whether RBMX is involved in retinal neuron apoptosis, we performed a light-induced retinal damage model in adult rats. Western blotting analysis showed RBMX gradually increased, reached a peak at 12 h and then declined during the following days. The association of RBMX in retinal ganglion cells (RGCs) with lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Previous studies have implicated light-induced damage in the progression of retinal degeneration focusing on the consequences of light-induced damage on cell function and homeostasis in the retina, noting changes in neural morphology, photoreceptor responsiveness, along with the induction of apoptosis 14 15 16 . It is well known that a consequence of photo-oxidative stress is an increase in the production of reactive lipid aldehydes, primarily 4HNE, leading to lipid peroxidation of retinal tissues and cytotoxic protein modifications in retinal cells 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have implicated light-induced damage in the progression of retinal degeneration focusing on the consequences of light-induced damage on cell function and homeostasis in the retina, noting changes in neural morphology, photoreceptor responsiveness, along with the induction of apoptosis 14 15 16 . It is well known that a consequence of photo-oxidative stress is an increase in the production of reactive lipid aldehydes, primarily 4HNE, leading to lipid peroxidation of retinal tissues and cytotoxic protein modifications in retinal cells 17 .…”
Section: Resultsmentioning
confidence: 99%
“…A previous study found that loss of mitochondrial DARS2 leads to the activation of various stress responses in a tissue-specific manner independently of respiratory chain deficiency [ 27 ]. The RBMX is a nuclear protein that is involved in alternative splicing of RNA [ 28 ]. It can confer resistance to DNA damage [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…139 Cleaved caspase-3 is elevated in RGC 6 h after toxic light exposure and reaches a peak after 3 days, 140–142 co-localising with increased staining for Ras homologue enriched in the brain (RHEB), cyclic AMP response element modulator-1 (CREM-1), transcription initiator factor IIB (TFIIB), pyruvate kinase isozyme type M2 (PKM2), SYF2 pre-mRNA splicing factor (SYF2) and RNA-binding motif protein, X-linked (RBMX), which are all involved in cell death pathways. 140–145 Nuclear factor of activated T cells, cytoplasmic 4 (NFATc4) (a component of T-cell activation and a regulator of the immune response) are also co-localised with cleaved caspase-3, caspase-8 and Fas-L in RGC, suggesting that NFATc4 may upregulate Fas-L and participate in RGC apoptosis. 146 Intravitreal mitogen-activated protein kinases/extracellular signal-regulated kinases (MAPK/ERK) inhibitor reduces PKM2 and active caspase-3 protein expression, suggesting that light-induced RGC apoptosis is in part dependent on MAPK/ERK pathway.…”
Section: Caspases and Rgc Deathmentioning
confidence: 99%